SR-ND-PB ISOTOPIC COMPOSITIONS OF PERIDOTITE XENOLITHS FROM SPITSBERGEN: NUMERICAL MODELLING INDICATES SR-ND DECOUPLING IN THE MANTLE BY MELT PERCOLATION METASOMATISM - Ionov D.A.; Mukasa S.B.; Bodinier J.-L. (My University, 2002)
Several spinel peridotite xenoliths from Spitsbergen have Sr–Nd isotopic compositions that plot to the right of the ‘mantle array’ defined by oceanic basalts and the DM end-member (depleted mantle, with low 87Sr/86Sr and high 143Nd/144Nd). These xenoliths also show strong fractionation of elements with similar compatibility (e.g. high La/Ce), which cannot be produced by simple mixing of light rare earth element-depleted peridotites with ocean island basalt-type or other enriched mantle melts. Numerical simulations of porous melt flow in spinel peridotites applied to Sr–Nd isotope compositions indicate that these features of the Spitsbergen peridotites can be explained by chemical fractionation during metasomatism in the mantle. ‘Chromatographic’ effects of melt percolation create a transient zone where the host depleted peridotites have experienced enrichment in Sr (with a radiogenic isotope composition) but not in Nd, thus producing Sr–Nd decoupling mainly controlled by partition coefficients and abundances of Sr and Nd in the melt and the peridotite. Therefore, Sr–Nd isotope decoupling, earlier reported for some other mantle peridotites worldwide, may be a signature of metasomatic processes rather than a source-related characteristic, contrary to models that invoke mixing with hypothetical Sr-rich fluids derived from subducted oceanic lithosphere. Pb isotope compositions of the Spitsbergen xenoliths do not appear to be consistently affected by the metasomatism.
Keywords: Spitsbergen; lithospheric mantle; metasomatism; radiogenic isotopes; theoretical modelling